Exploring the cultural, ritual, spiritual, and social significance of the Mebuug-Buugan tradition as a unique Balinese heritage practice - Sadiyani, Ni Wayan; Sutiarso, M. Agus; Amarachi, Ofordi Joy; Hassan, A.M.M. Mahmudul (Yayasan Mitra Persada Nusantara, 2025)
The existence of traditional arts today serves not only as a cultural identity of a region but also as a dynamic force that influences the life and values of the local community. Traditions that are rooted in a particular area emerge through a long historical and cultural journey, eventually becoming systems of belief and habitual practice. The shared perspectives and local mythologies that form the basis of these traditions often reflect the creativity and local genius of the community. One such revitalized tradition is Mebuug-Buugan in Adat Kedonganan Village, Kuta District, Badung Regency, Bali, which was reconstructed in 2014 after being absent for nearly 60 years. The aim of this study is to explore the philosophical and social meanings embedded within the Mebuug-Buugan tradition, and to assess how it embodies the principles of local wisdom, especially in relation to Tri Hita Karana, the Balinese philosophy of harmonious living. Using a qualitative descriptive method, this research relies on data gathered through observation, interviews, and document studies related to the tradition’s implementation, symbols, and community participation. The analysis reveals that Mebuug-Buugan, a mud-based ritual conducted in mangrove areas after the Nyepi celebration, is not merely a traditional game but a symbolic act of self-purification, environmental harmony, and social cohesion. The ritual’s reconstruction has strengthened the community’s cultural identity, revitalized environmental awareness, and reestablished social harmony rooted in ancestral values. In conclusion, Mebuug-Buugan is a valuable cultural expression that reflects deep spiritual and ecological meanings. Its revitalization affirms the resilience of Balinese traditions in the modern era and highlights the importance of preserving local wisdom through collective community action.